Unveiling correlations between aristolochic acids and liver cancer: spatiotemporal heterogeneity phenomenon - Chengxian Li; Xinyu Li; Ming Niu; Dake Xiao; Ye Luo; Yinkang Wang; Zhi-E. Fang; Xiaoyan Zhan; Xu Zhao; Mingxia Fang; Jiabo Wang; Xiaohe Xiao; et al. (BMC, 2024)
Abstract Aristolochic acids are a class of naturally occurring compounds in Aristolochiaceae that have similar structural skeletons and chemical properties. Exposure to aristolochic acids is a risk factor for severe kidney disease and urinary system cancer. However, the carcinogenicity of aristolochic acids to the liver, which is the main site of aristolochic acid metabolism, is unclear. Although the characteristic fingerprint of aristolochic acid-induced mutations has been detected in the liver and aristolochic acids are known to be hepatotoxic, whether aristolochic acids can directly cause liver cancer is yet to be verified. This review summarizes the findings of long-term carcinogenicity studies of aristolochic acids in experimental animals. We propose that spatiotemporal heterogeneity in the carcinogenicity of these phytochemicals could explain why direct evidence of aristolochic acids causing liver cancer has never been found in adult individuals. We also summarized the reported approaches to mitigate aristolochic acid-induced hepatotoxicity to better address the associated global safety issue and provide directions and recommendations for future investigation.